2018
DOI: 10.1186/s13569-018-0106-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative radiotherapy of soft-tissue sarcomas: surgical and radiologic parameters associated with local control and survival

Abstract: BackgroundPreoperative radiotherapy is often used to facilitate excision of soft-tissue sarcomas. We aimed define factors that affect local tumour control and patient survival.MethodsA single institution registry study of 89 patients with non-metastatic soft-tissue sarcomas having preoperative radiotherapy between 1994 and 2014. Radiologic (presence of peritumoural oedema and volume change following radiotherapy) and histopathologic (tumour volume, grade and surgical margin) parameters were recorded. Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…26,27 Furthermore, current NCCN guidelines encourage consideration of radiation in the neoadjuvant setting for all extremity sarcomas in which radiation therapy is planned, as neoadjuvant radiation has been shown to be associated with improved complete resection rates and functional outcomes. 18,21,28,29 It is perhaps not surprising that neoadjuvant radiation was not directly associated with improved survival in this study, given similar results shown in multiple other prospective trials in sarcoma. 8,11 Even so, the association demonstrated in this study between complete (R0) angiosarcoma resection and survival may be important, and is largely concordant with multiple prior studies which have demonstrated that margin negative resection is a prognostically significant outcome in sarcoma management.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…26,27 Furthermore, current NCCN guidelines encourage consideration of radiation in the neoadjuvant setting for all extremity sarcomas in which radiation therapy is planned, as neoadjuvant radiation has been shown to be associated with improved complete resection rates and functional outcomes. 18,21,28,29 It is perhaps not surprising that neoadjuvant radiation was not directly associated with improved survival in this study, given similar results shown in multiple other prospective trials in sarcoma. 8,11 Even so, the association demonstrated in this study between complete (R0) angiosarcoma resection and survival may be important, and is largely concordant with multiple prior studies which have demonstrated that margin negative resection is a prognostically significant outcome in sarcoma management.…”
Section: Discussionsupporting
confidence: 76%
“…Small institutional studies of head and neck angiosarcoma have shown a utility of radiotherapy with improvement in local control 15,16 and OS. 15,17 Neoadjuvant radiation (NRT) has gained increasing popularity in the management of soft tissue extremity sarcoma, with its potential advantages of improving rates of complete tumor resection 18 and function preservation. 19 To what extent neoadjuvant radiation is used for cutaneous and soft tissue angiosarcoma, and its impact on short-and long-term oncologic outcomes remain understudied.…”
mentioning
confidence: 99%
“…This approach involves case-by-case multidisciplinary discussion, reimaging and offering a re-excision with curative intention when possible. Even though the use of neo-adjuvant radiotherapy has been described for previous incomplete resections 19 , our experience suggests that a wide excision leads to similar outcomes with patients that obtained clear margins in the first instance. We believe that the role of reconstructive surgery for the treatment of sarcomas is to facilitate these adequate oncological resections, by means of providing immediate resurfacing of the resulting large defects.…”
Section: Discussionmentioning
confidence: 66%
“…Nevertheless, the use of PN as a clinically meaningful surrogate is controversial, because other investigators have found no association between pathologic response and oncologic outcomes, 11 , 12 , 13 even when stratified with the endpoints of PN ≥95% 14 , 15 , 16 or ≥80%. 17 However, these series were limited by smaller sample sizes and confounded by a number of patients receiving concurrent chemotherapy.…”
Section: Introductionmentioning
confidence: 99%